Analysis of Tin Stock Investment Projections during the Covid-19 Pandemic - Ari Agung Nugroho; Sumar Sumar; Khairiyansyah Khairiyansyah; Doni Yanuar (Garuda Prestasi Nusantara Consulting, 2023)
Indonesia and other countries in the world are still experiencing the Covid-19 pandemic and continue to struggle for the country's health and economic recovery. The government along with all elements of society are tackling the impact of Covid-19 by implementing 3M (wearing masks, washing hands, maintaining distance), implementing health protocols, vaccination programs and implementing Large-Scale Social Restrictions (PSBB). The community collaborates on advances in smartphone technology with PSBB activities in their daily activities. With the advancement of technology platforms, it is very easy for people to transact in the stock investment mechanism and have an impact on people's lives. 99% of Indonesia's tin mineral potential is in the Bangka Belitung Archipelago Province, while the rest is in the Riau Islands, Riau and West Kalimantan. The economic condition of the Bangka Belitung Islands province is still supported by the mining and quarrying sector, especially tin mining and the tin processing industry, in line with Irawan's study. So the tin stock investment instrument is still one of the instrument models that can be used during the Covid 19 pandemic. In the world of stock investment, there are two types of analysis known, namely fundamental analysis and technical analysis. Technical analysis attempts to test historical data in predicting stock prices in order to buy or sell an investment instrument. Keywords: Covid 19, Stocks, Tin, Investment